Sanz, J. L. .(1999). Mitología de los Dinosaurios. Edit. Taurus. 206 págs - M. Carmen de Lemus Varela (Universidad de La Rioja, 2013)
Sanz, J. L. .(1999). Mitología de los Dinosaurios. Edit. Taurus. 206 págs.